The multi-objective multi-item just-in-time transportation problem. (16th December 2022) - Mardanya, Dharmadas; Maity, Gurupada; Kumar Roy, Sankar
Abstract : This paper analyses the study of Just-in-Time transportation problem with multi-item under multi-objective environment. Realizing the impact of time in a real-life transportation problem, here we introduce the concept of Just-in-Time which helps to extract the optimum network for transporting goods from origins to destinations in scheduled time. The model of multi-objective multi-item Just-in-Time transportation problem is formulated, and then an algorithm is developed under some priority-based approaches to obtain a Pareto optimal solution. To test and justify the efficiency of our study, we include a practical example having three-fold priority: (i) first priority is to deliver goods within the scheduled time, (ii) second priority is to minimize the total transportation cost, and (iii) third priority is to maximize the profit. Finally, the paper ends with the conclusions and future study.